A Nanostructured Mo2C‐rGO Heterostructure as a stable Anode with ultra‐high capacity for Lithium‐Ion Battery. Issue 6 (9th February 2022) - Kanade, Sandeep C.; Ambalkar, Anuradha A.; Sethi, Yogesh A.; Thotiyl, Musthafa Ottakam; Kale, Bharat B.; Gambhire, Anil B.
Abstract: In the present work, we have demonstrated the synthesis of Molybdenum Carbide‐reduced graphene oxide (Mo2 C‐rGO) heterostructure. Uniquely, the in‐situ formation of rGO using D‐glucose in the heterostructure and its battery performance has been discussed. The High Resolution Transmission Electron Microscopy (HR‐TEM) study clearly shows the growth of Mo2 C nanoparticles along with rGO confers a unique integrated layered heterostructure. X‐ray diffraction (XRD) and Raman study exhibits the formation of graphene oxide (GO) followed by multi‐layers of rGO along with hexagonal Mo2 C. The electrochemical study of Mo2 C‐rGO heterostructure demonstrates stable cycling performance and excellent rate capabilities. The heterostructure showed the initial capacity (1st discharge) around 632.23 mAh/g and specific capacity i. e., 537.91 mAh/g @ 0.5 A/g with 99–100 % columbic efficiency. The reversible capacities of 521.56 mAh/g, and 400.76 mAh/g were observed at current densities of 1 A/g and 2 A/g for 300 cycles, respectively, which justifies the stability of heterostructure. The cycled cell was investigated by using Electrochemical Imepedance Spectroscopy (EIS), ex‐situ XRD, and Field Emmision Scanning Electron microscopy (FESEM), which shows the negligible change in the ionic conductivity, structure, and morphology after 300 cycles. It shows the excellent stability of Mo2 C‐rGO heterostructure. Abstract : Robust Anode material for Li‐ion battery The robust Molybdenum Carbide‐reduced graphene oxide (Mo2 C‐rGO) synthesized by hydrothermal carburization method, used as anode in Li‐ion (Li + ) half cell, where it remains stable after 300 cycles of charging‐discharging. Lithium metal foil (Li‐Foil) used as counter electrode. The stable reversible specific capacities of 521.56 mAh/g, and 400.76 mAh/g were achieved at current densities of 1 A/g and 2 A/g.